Status nauki wychodzącej z subiektywności i intencjonalności - refleksje (fenomenologie jako teoretyczna ariergarda podmiotu a problem naukowości analiz) = The status of science originating from subjectivity and intentionality - the reflection (phenomenology as the theoretical rearguard of the subject versus the scientific character of the analyzes) - Kowalski, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present problem areas in a synthetic way and to indicate the issues that arise when determining the status of science in terms of subjectivity and intentionality of experience and analysis. The research question was as follows: what issues should be considered in the socio-humanistic (incl. pedagogical) reflection around the triad: science - subjectivity - intentionality. The article attempts to define an analytical and critical framework of the discussion about the subject and the directions of theoretical analyzes. The author`s aim is also to outline practical references of contemporary research issues.
Keywords: nauka; subiektywność; podmiot; intencjonalność; subjectivity; science; subject; intentionality